Evidence of disparities in the provision of the maternal postpartum 6-week check in primary care in England, 2015–2018: an observational study using the Clinical Practice Research Datalink (CPRD). Issue 3 (9th September 2021) - Li, Yangmei; Kurinczuk, Jennifer J; Gale, Christopher; Siassakos, Dimitrios; Carson, Claire
Abstract : Background: A maternal postpartum 6-week check (SWC) with a general practitioner (GP) is now considered an essential service in England, a recent policy change intended to improve women's health. We aimed to provide an up-to-date snapshot of the prevalence of SWC prior to the policy change as a baseline, and to explore factors associated with having a late or no check. Methods: We conducted a cohort study using primary care records in England (Clinical Practice Research Datalink (CPRD)). 34 337 women who gave birth between 1 July 2015 and 30 June 2018 and had ≥12 weeks of follow-up post partum were identified in the CPRD Pregnancy Register. The proportion who had evidence of an SWC with a GP was calculated, and regression analysis was used to assess the association between women's characteristics and risks of a late or no check. Results: Sixty-two per cent (95% CI 58% to 67%) of women had an SWC recorded at their GP practice within 12 weeks post partum, another 27% had other consultations. Forty per cent had an SWC at the recommended 6–8 weeks, 2% earlier and 20% later. A late or no check was more common among younger women, mothers of preterm babies or those registered in more deprived areas. Conclusions: Nearly 40% of women did not have a postpartum SWC recorded. Provision or uptake was not equitable; younger women and those in more deprived areas were less likely to have a record of such check, suggesting postpartum care in general practice may be missing some women who need it most.